Incorporación de níquel a catalizadores Hf-SBA-15 y su efecto sobre las rutas de reacción en la conversión de furfural - Chávez Nambo, Jafet (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
In this work, the transformation of furfural (FUR), a hemicellulose -derived compound, into furfuryl alcohol (FOH) and (propan-2-yloxymethyl)furan was studied through catalytic transfer hydrogenation (CTH) using isopropanol as a hydrogen donor. For this purpose, bifunctional catalysts of the type Ni(y)/Hf-SBA-15(x) were synthesized. In the first stage, Hf-SBA-15(x) materials were prepared by the sol-gel method, employing Si/Hf molar ratios of 20 and 40; subsequently, different amounts of Ni (0, 1.5, and 2.5 wt%) were incorporated by incipient wetness impregnation. The materials were characterized by SAXRD, ICP-OES, nitrogen physisorption, UV-Vis-DRS, SEM, and NH₃-TPD. The results demonstrated that the incorporation of Hf into the SBA-15 support promotes the generation of Lewis acid sites, essential for FUR activation, whereas Ni, in conjunction with these acid sites, induces the formation of (propan-2-yloxymethyl)furan. With the acidic Hf-SBA-15 catalysts, FUR conversions close to 100% were achieved, showing that the Si/Hf=40 ratio, with more moderate acidity, favored selectivity toward FOH, while Si/Hf=20 accelerated the conversion but with a higher contribution from cons ecutive routes toward (propan-2-yloxymethyl)furan. In contrast, Ni/Hf-SBA-15 catalysts markedly promoted the formation of (propan-2-yloxymethyl)furan, with Ni(1.5)/Hf-SBA- 15(40) being the most selective toward this product. Kinetic analysis using a pseudo -firstorder model satisfactorily fitted the experimental distribution of reactants and products. The estimated parameters showed that the acidic Hf-SBA-15(x) catalysts exhibited k₁/k₂ ratios greater than 4, indicating that FOH formation was strongly favored over (propan-2- yloxymethyl)furan, whereas Ni/Hf-SBA-15 catalysts displayed k₁/k₂ values close to 0.15, reflecting the high selectivity toward (propan-2-yloxymethyl)furan. Overall, these results demonstrate that the controlled incorporation of Hf and Ni i nto SBA-15 enables modulation of the reaction pathways and directs FUR conversion toward high -value products such as FOH and (propan-2-yloxymethyl)furan.

En este trabajo se estudió la transformación de furfural (FUR), un derivado de la hemicelulosa, hacia alcohol furfurílico (FOH) y (propan -2-iloximetil)furano mediante hidrogenación vía transferencia catalítica (CTH) empleando isopropanol como donador de hidrógeno. Para ello se sintetizaron catalizadores bifuncionales del tipo Ni(y)/Hf-SBA- 15(x). En una primera etapa se prepararon materiales Hf-SBA-15(x) mediante el método sol-gel, utilizando relaciones molares Si/Hf de 20 y 40; posteriormente se incorporaron diferentes cantidades de Ni (0, 1.5 y 2.5 % peso) por impregnación húmeda incipiente. Los materiales fueron caracterizados por SAXRD, ICP-OES, fisisorción de nitrógeno, UVVis- DRS, SEM y TPD de NH₃. Los resultados demostraron que la incorporación de Hf al soporte SBA-15 promueve la formación de sitios ácidos de Lewis, esenciales para la activación del FUR, mientras que el Ni, en conjunto con dichos sitios ácidos, induce la formación de (propan-2-iloximetil)furano. Con los catalizadores ácidos Hf-SBA-15, se alcanzaron conversiones de FUR cercanas al 100 %, observándose que la relación Si/Hf=40, con acidez más moderada, favoreció la selectividad hacia FOH, mientras que Si/Hf=20 aceleró la conversión, pero con mayor contribución de rutas consecutivas hacia (propan-2-iloximetil)furano. En contraste, los catalizadores Ni/Hf-SBA-15 promovieron de manera marcada la formación de (propan-2-iloximetil)furano, siendo el material Ni(1.5)/Hf-SBA-15(40) el más selectivo a este producto. El análisis cinético mediante un modelo de pseudo-primer orden permitió ajustar satisfactoriamente la distribución experimental de reactivos y productos. Los parámetros estimados mostraron que los catalizadores ácidos Hf-SBA-15(x) presentan relaciones k₁/k₂ > 4, lo que indica que la formación de FOH es mucho más favorecida frente a la de (propan-2-iloximetil)furano, mientras que los catalizadores Ni/Hf-SBA-15 exhibieron valores k₁/k₂ cercanos a 0.15, reflejando la alta selectividad hacia (propan-2-iloximetil)furano. En conjunto, estos resultados evidencian que la incorporación controlada de Hf y Ni al soporte SBA-15 permite modular las rutas de reacción y dirigir la conversión de FUR hacia productos de valor agregado como FOH y (propan-2-iloximetil)furano.
Facultad de Ingeniería Química. Maestría en Ciencias en Ingeniería Química
Keywords: info:eu-repo/classification/cti/7; FIQ-M-2025-1437; Catálisis heterogénea; Hidrogenación vía transferencia catalítica; Alcohol furfurílico; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19450